2014
DOI: 10.1111/cpf.12193
|View full text |Cite
|
Sign up to set email alerts
|

Acute resistance exercise with blood flow restriction effects on heart rate, double product, oxygen saturation and perceived exertion

Abstract: The aim of this study was to compare the acute effect of resistance exercise (RE) with and without blood flow restriction (BFR) on heart rate (HR), double product (DP), oxygen saturation (SpO2 ) and rating of perceived exertion (RPE). Twenty-four men (21·79 ± 3·21 years) performed three experimental protocols in a random order (crossover): (i) high-intensity RE at 80% of 1RM (HI), (ii) low-intensity RE at 20% of 1RM (LI) and (iii) low-intensity RE at 20% of 1RM combined with partial blood flow restriction (LI+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
69
2
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(84 citation statements)
references
References 37 publications
9
69
2
3
Order By: Relevance
“…The primary results of the present study were as follows: i) the three groups exhibited increased SBP, HR and DP but did not exhibit differences on SpO2; ii) the LL and LL+BFR treatments resulted in greater hemodynamic increases compared with the HI treatment; and iii) the phases of the MC seem to influence only HR and DP. Nonetheless, we observed a significant increase in SBP, HR and DP among the three exercise groups, and between the few studies that evaluated these variables after RE with BFR (Araújo et al, 2014;Brandner, Kidgell, & Warmington, 2015;Neto et al, 2016;Okuno et al, 2014), two corroborate with our findings (Brandner et al, 2015;Neto et al, 2016). These authors reported increased SBP, DBP and MBP (Brandner et al, 2015) and HR and DP (Brandner et al, 2015;Neto et al, 2016) immediately after LL with BFR and after LL and HI exercises.…”
Section: Oxygen Saturation (Spo2)supporting
confidence: 90%
See 3 more Smart Citations
“…The primary results of the present study were as follows: i) the three groups exhibited increased SBP, HR and DP but did not exhibit differences on SpO2; ii) the LL and LL+BFR treatments resulted in greater hemodynamic increases compared with the HI treatment; and iii) the phases of the MC seem to influence only HR and DP. Nonetheless, we observed a significant increase in SBP, HR and DP among the three exercise groups, and between the few studies that evaluated these variables after RE with BFR (Araújo et al, 2014;Brandner, Kidgell, & Warmington, 2015;Neto et al, 2016;Okuno et al, 2014), two corroborate with our findings (Brandner et al, 2015;Neto et al, 2016). These authors reported increased SBP, DBP and MBP (Brandner et al, 2015) and HR and DP (Brandner et al, 2015;Neto et al, 2016) immediately after LL with BFR and after LL and HI exercises.…”
Section: Oxygen Saturation (Spo2)supporting
confidence: 90%
“…Nonetheless, we observed a significant increase in SBP, HR and DP among the three exercise groups, and between the few studies that evaluated these variables after RE with BFR (Araújo et al, 2014;Brandner, Kidgell, & Warmington, 2015;Neto et al, 2016;Okuno et al, 2014), two corroborate with our findings (Brandner et al, 2015;Neto et al, 2016). These authors reported increased SBP, DBP and MBP (Brandner et al, 2015) and HR and DP (Brandner et al, 2015;Neto et al, 2016) immediately after LL with BFR and after LL and HI exercises. Thus, we concluded that the increased values observed in the present study are within the normal patterns, which reinforces the safety of both continuous and intermittent BFR (Brandner et al, 2015).…”
Section: Oxygen Saturation (Spo2)supporting
confidence: 90%
See 2 more Smart Citations
“…As pesquisas mostram sua eficácia sobre variáveis neuromusculares, como os ganhos de força e hipertrofia muscular (Pearson & Hussain, 2015), hormonais (Inagaki, Madarame, Neya, & Ishii, 2011), metabólicas (Burgomaster et al, 2003;Fujita et al, 2007), hemodinâmicas (Araújo et al, 2014;Brandner, Kidgell, & Warmington, 2014;Neto et al, 2015;Neto et al, 2016;Okuno, Pedro, Leicht, Ramos, & Nakamura, 2014;Rossow et al, 2011;Vieira, Chiappa, Umpierre, Stein, & Ribeiro, 2013) e complacência arterial (Iida et al, 2011;Iida et al, 2005).…”
Section: Introductionunclassified